Pengembangan Perangkat Pembelajaran Sistem Persamaan Linear Dua Variabel Melalui Pendekatan Realistic Mathematic Education - Sapi'i Sapi'i (Jurnal Paedagogy, 2020)
The purpose of this study was to develop a mathematics learning tool on the material system of two-variable linear equations through the RME (Realistic Mathematic Education) approach. This research is a development research adopting a 4-D model with the following stages of research: 1) definition, 2) design, 3) development, and 4) deployment. Learning tools developed include Learning Implementation Plans and Student Worksheets. The quality of the model is measured based on three aspects, namely valid, practical and effective. Model validation is done by an expert by looking at two aspects, namely the content or content and use of language. Practicality of the model is measured based on three aspects, namely (1) learning activities in the classroom, and (2) student responses to the implementation of learning tools, while the effectiveness of the model is measured through the implementation of the model to see student learning outcomes. The results showed that the learning tools developed were valid but needed to be revised on several items / components. Learning tools are already practicable as indicated by the average response of students to learning through the Realistic Mathematic Education approach of 3.94 with good categories, and student activities during learning reach 92.8% with active categories. Learning tools developed are effective for improving student learning outcomes as indicated by the number of students who achieve mastery learning by 75% while those who have not completed by 25%.